PENALTIES FOR DELAYED CONTRACT COMPLETION IN THE SAMBAS DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING: AN ISLAMIC LEGAL PERSPECTIVE - Elin Farlina, Uray (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
The government's procurement of goods and services entails inherent rights and responsibilities for all parties involved, including government entities, individual contractors, and organizations. Within the Department of Public Works and Spatial Planning in Sambas, delays in contract execution are a common occurrence, leading to the imposition of penalties on contractors. In Islamic jurisprudence, it is emphasized that lease agreements should explicitly specify both the duration and compensation at the outset of the contract, rather than after work has commenced. Deviations from these contractual terms are considered religiously impermissible. This research has two primary objectives: (1) to investigate the application of penalties for contract delays within the Department of Public Works and Spatial Planning in Sambas, and (2) to assess the conformity of these penalties with Islamic law. This study adopts a field research approach and employs a descriptive analytical method for data analysis. The study findings indicate that (1) the Department of Public Works and Spatial Planning in Sambas conducts thorough investigations, assessments, and surveys before imposing penalties for delays, in compliance with regulations outlined in Presidential Regulation No. 16 of 2018, Article 79, paragraph (4); (2) The penalties for contract delays do not entirely align with Islamic law, primarily due to disparities between the agreed-upon timeframe and the actual execution, potentially rendering contracts invalid in the context of construction service agreements and Ijaratul a’mal.